2017
DOI: 10.1111/evj.12701
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after medical and surgical interventions in horses with temporohyoid osteoarthropathy

Abstract: The survival prognosis in horses with THO is good to excellent in those submitted to surgical intervention, and fair in those treated with medical therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 17 publications
(59 reference statements)
3
20
0
Order By: Relevance
“…Clinical signs of THO resolved in all clinical surgically treated horses in the context of this study, and horses returned to their previous levels of performance. This is in agreement with findings reported in previous studies in which CHE was performed under general anesthesia with 65% to 80% of horses returning to performance following surgery . Important intraoperative hemorrhage can occur during the CHE procedure .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Clinical signs of THO resolved in all clinical surgically treated horses in the context of this study, and horses returned to their previous levels of performance. This is in agreement with findings reported in previous studies in which CHE was performed under general anesthesia with 65% to 80% of horses returning to performance following surgery . Important intraoperative hemorrhage can occur during the CHE procedure .…”
Section: Discussionsupporting
confidence: 92%
“…With horses placed in dorsal recumbency under general anesthesia, pooling of blood in a deep incision can complicate accurate placement of hemostatic forceps, and hematomas may form during or after the recovery from anesthesia. This may explain the requirement for a blood transfusion because of profuse hemorrhage in one horse operated on in dorsal recumbency in a previous study by Espinosa and colleagues . Furthermore, in that same study in horses operated on under general anesthesia, three horses developed dyspnoea after surgery and required a tracheostomy.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…A recent retrospective study comparing treatment interventions demonstrated a significantly improved survival prognosis in those horses that were subject to surgery over those that were treated medically (Espinosa et al 2017). Several surgical options for the treatment of THO are described; these include a partial stylohyoid ostectomy (PSHO) and a CHO (Divers et al 2006;Freeman and Hardy 2012;Oliver and Hardy 2015).…”
Section: Introductionmentioning
confidence: 99%